Numerical modeling of a CdS/CdTe photovoltaic cell based on ZnTe BSF layer with optimum thickness of absorber layer. Issue 1 (1st January 2017) - Safa Sultana, Rucksana; Bahar, Ali Newaz; Asaduzzaman, Md.; Ahmed, Kawsar
Abstract: High efficiency ultrathin CdTe film is an excellent candidate for reliable, efficient, stable and low cost solar cells. In this paper, a high efficiency CdS/CdTe solar cell has been studied by using ADEPT 1D simulation tool. The proposed device has been simulated with a reduced CdTe absorber layer thickness and a ZnTe layer as back surface field (BSF) which substantiates sensible energy conversion efficiency. The investigation into the simulation results showed that the conversion efficiency with BSF layer and 1 μm thick CdTe absorber is 8.24% more as compared to the conventional CdTe cells (without BSF layer). Reduction of minority carrier recombination loss due to the insertion of BSF layer at the back contact in ultra-thin CdS/CdTe cells has also been investigated. The results depict that CdTe cell with BSF layer is responsible for increasing the quantum efficiency. However, the proposed structure of ZnO/CdS/CdTe/ZnTe demonstrates the highest efficiency of 24.66% ( V oc = 946.51 mV, J sc = 34.40 mA/cm 2 and FF = 75.72%) under global AM1.5G illumination spectra.